A Holistic Methodology for Probabilistic Safety Assessment of Timber Elements Combining Onsite and Laboratory Data. Issue 5 (3rd July 2016) - Sousa, Hélder S.; Branco, Jorge M.; Lourenço, Paulo B.
ABSTRACT: The assessment of existing timber structures comprises several fields of knowledge, each one providing its own piece of information aiming at an effective answer. Even if general guidelines are available, there is still a need for a holistic approach that is able to combine information from different sources and infer upon that information allowing also, in that process, for an updating scheme aiming at a more substantiated decision process. In that scope, this article proposes a methodology for a holistic assessment of timber elements. The methodology combines information gathered in different scales and follows a probabilistic framework that allows for the structural assessment of existing timber elements with possibility of inference and updating of the mechanical properties of the elements, through Bayesian methods. The described methodology is based in four main steps: (i) scale of information; (ii) local and global data; (iii) probability assignment; and (iv) long-term structural analysis. After the description of the methodology, its limitations and possible future modifications are discussed.